2021
DOI: 10.3233/jad-200734
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Amyloid Pathology in Mild Cognitive Impairment Using Radiomics Analysis of Magnetic Resonance Imaging

Abstract: Background: Noninvasive identification of amyloid-β (Aβ) is important for better clinical management of mild cognitive impairment (MCI) patients. Objective: To investigate whether radiomics features in the hippocampus in MCI improve the prediction of cerebrospinal fluid (CSF) Aβ42 status when integrated with clinical profiles. Methods: A total of 407 MCI subjects from the Alzheimer’s Disease Neuroimaging Initiative were allocated to training (n = 324) and test (n = 83) sets. Radiomics features (n = 214) from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“… 22 Another study performed the same task with only T1-MRI. 23 Both were able to achieve an AUC close to 0.75. Some diagnostic studies demonstrated an advantage of using multimodality data, 22 and many found that features from the MTL regions emerged as the most informative, similar to findings in the prognostic studies.…”
Section: Use Of Traditional Radiomics In Adrd Neuroimagingmentioning
confidence: 92%
“… 22 Another study performed the same task with only T1-MRI. 23 Both were able to achieve an AUC close to 0.75. Some diagnostic studies demonstrated an advantage of using multimodality data, 22 and many found that features from the MTL regions emerged as the most informative, similar to findings in the prognostic studies.…”
Section: Use Of Traditional Radiomics In Adrd Neuroimagingmentioning
confidence: 92%
“…108 Using radiomics models from MRI can help predict amyloid positivity in patients with MCI. 109 We summarised the structural MRI regions associated with pAD in table 3. Some other MRI technologies, such as resting-state functional MRI and diffusion tensor imaging, as well as novel AI-based approaches, such as machine learning and convolutional networks, have improved the accuracy of MRI for the diagnosis of pAD.…”
Section: Mrimentioning
confidence: 99%
“…Converging evidence highlights the potential of radiomics approaches to serve as neuroimaging biomarkers in the field of the neurodegenerative brain (9)(10)(11)(12). This narrative review presents the last progress and potential application of radiomics in the field of neurodegenerative nuclear imaging focusing mainly on positron-emission tomography (PET) and singlephoton emission computerized tomography (SPECT) with different radiotracers.…”
Section: Introductionmentioning
confidence: 99%